The Intersection of Digital Rights and Reproductive Rights: Legal Implications and Challenges in the Digital Age - Sibongile Gobile; Erica Afrihyia; Olufunke Omotayo; Ashiata Yetunde Mustapha; Opeoluwa Oluwanifemi Akomolafe; Adelaide Yeboah Forkuo (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
In the rapidly evolving digital age, the intersection of digital rights and reproductive rights has become increasingly complex, posing significant legal implications and challenges. This paper explores the intricate relationship between digital technologies and reproductive health, shedding light on the legal frameworks governing these domains and the emerging issues at their intersection. The analysis encompasses the privacy concerns surrounding accessing reproductive health information online, the role of digital platforms in disseminating reproductive health education and services, and the impact of technological advancements such as telemedicine and fertility tracking apps on reproductive rights. Furthermore, the paper delves into the complexities of data protection, addressing the challenges in safeguarding sensitive reproductive health data in the digital sphere. Through case studies and legal analysis, it examines the existing laws and regulations, including the GDPR and HIPAA, and their applicability to digital reproductive health services. International perspectives are also explored, highlighting variations in legal frameworks and their implications for digital reproductive rights globally. The paper identifies regulatory gaps, data privacy concerns, accessibility barriers, and ethical considerations as key challenges in the digital age. It proposes strategies and solutions to address these challenges, including policy recommendations, the strengthening of legal frameworks, multi-stakeholder collaboration, and efforts to empower individuals through education and advocacy. By critically examining the intersection of digital rights and reproductive rights, this paper contributes to the ongoing discourse on human rights, gender equality, and public health in the digital era.
Keywords: Digital rights; Reproductive rights; Legal implications; Challenges; Privacy concerns; Technological advancements